PENGARUH KUALITAS PELAYANAN TERHADAP MINAT KONSUMEN PADA RAMAYANA LESTARI SENTOSA PEKANBARU - Ananda, Indra; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aimed to determine the effect of service quality on consumen interest of Ramayana Lestari Sentosa Pekanbaru.service quality as an independent variable (X).while consumen interest as the dependent variable (Y). study was conducted on consumen in Ramayana Lestari Sentosa Pekanbaru by 100 people.Data obtained from the questionnaire and further processed and tested using statistical analysis such as simple regression analysis , t test, correlation analysis and determination using SPSS program.The results showed that the test results of hypothesis testing. tcount(11.979) >ttable (1.984 ) This suggest that the service quality affect the consumen interest. The magnitude of the service quality on consumen interest in Ramayana Lestari Sentosa Pekanbaru is 59%.Keyword: service quality, consumen interest & Empaty